Biochar Based Soil Amendment Formulation for Improvement Upland Acidic Soil in East Lampung: Soil Properties and Maize (Zea Mays) Yield - Neneng Laela Nurida; . Jubaedah (UNIVERSITY OF LAMPUNG, 2019)
Many of soil amendment formulations (as a biochar based) have been tested in Indonesian Soil Research Institute greenhouse experiment to improve its effectiveness in the soil, though field experiments were still needed to measure more about its effectiveness. The objectives of this research are to study biochar-based soil amendment formulation on different ways of application in improving soil properties and crop yield in upland acidic soil. The research was conducted in Taman Bogo Research Station, East Lampung during three planting seasons. It started at January 2013 and finished at January 2014. The study was arranged in a split plot design with 3 replications. The main plot was 3 types of soil amendment formula namely SP50, SP75 and KS50. The subplot was the biochar-based soil amendment application way (7.5 Mg ha-1 per planting seasons), which gradually applied to soil namely three times of 3 planting seasons (2.5-2.5- 2.5 Mg ha-1), two times of 3 planting seasons (5.0-2.5-0 Mg ha-1), and a single time in 3 planting seasons (7.5-0-0 Mg ha-1). The plant indicator was maize (Zea mays), Bisma variety. The variables observed were soil physical and chemical properties, and also maize yield. The results showed that during three planting seasons, the three types of soil amendment formulas had no effect on soil physical properties (Bulk density/BD and plant available water pores/AWP) and soil chemical properties (soil pH, organic C, K2+, Ca2+ and Al3+), and maize yield. Biochar gradual application in two times (5.0-2.0-0 Mg ha-1) and a single time (7.5-0-0 Mg ha-1) had more effects and consistently improve AWP, soil chemical properties, and dry grain during 3 planting seasons compared to the application of 3 times in 3 planting seasons (2.5-2.5- 2.5 Mg ha-1). The dried grain yield was 3.11-5.23 Mg ha-1 per season or it was increased 291% in average during three planting seasons. Biochar application at a single time (at the beginning of the season at the rate of 7.5-0-0 Mg ha-1) provided positive residual effects on both soil and crop in upland acidic soil of East Lampung.